Haptoglobin as a supplement in in vitro embryo culture: a tool for improving bovine embryo development and quality - Karina Cañón-Beltrán; Yulia N. Cajas; Cristina Martínez-López; Carla Moros-Nicolás; Pilar Sòria-Monzó; Miriam Balastegui-Alarcón; Manuel Avilés; Dimitrios Rizos; Francisco A. García-Vázquez; Mª José Izquierdo-Rico (Biological Research)
Abstract Background Recent studies have indicated the potential involvement of haptoglobin in a variety of events during mammalian reproduction, with previous research highlighting its efficacy in promoting porcine embryo development. The present study aims to provide a comprehensive investigation of haptoglobin expression and secretion in the bovine uterus, with a view to assessing its impact on bovine in vitro embryo production. A systematic study was conducted on cows in different oestrous stages, early follicular, late follicular, early luteal and late luteal stages. Relative haptoglobin mRNA abundance was quantified by RT-qPCR, and the expression of the protein was analysed by immunohistochemistry. The results were complemented by proteomic analyses of the uterine fluid. In vitro bovine fertilisation and embryo culture were carried out in the presence of haptoglobin. Results Haptoglobin mRNA expression in the bovine uterus is most abundant during the late luteal stage of the oestrous cycle. The presence of haptoglobin was demonstrated in the uterine epithelium and the uterine fluid in different stages of the oestrous cycle by immunohistochemistry and proteomic analyses. Furthermore, the addition of haptoglobin to in vitro culture improved the development of bovine embryos when the protein was present on the days corresponding to its passage through the uterus, with a higher blastocyst yield (P < 0.05) being observed in haptoglobin treatments compared with control groups. Haptoglobin appears to influence embryonic development by reducing mitochondrial activity and lipid content. Furthermore, transcripts associated with oxidative stress, lipid metabolism and cell cycle regulation were affected by the presence of haptoglobin. Conclusions The presence of haptoglobin protein in the female tract of cows during different stages of the oestrous cycle suggests that it plays a significant role in the reproductive process. The addition of haptoglobin during in vitro embryo production resulted in enhanced blastocyst rates and improved quality.